Three essays on corporate finance and research methodology - Li, Wei (Nanyang Technological University, 2020)
My dissertation includes topics in corporate finance and research methodology. It contains three chapters. Chapter one aims to understand whether investor-paid credit rating agency (CRA) can improve rated firms’ information transparency. It has two main findings. First, the coverage of Egan Jones Ratings (EJR) – an investor-paid CRA – leads to an increase in rated firms’ stock price informativeness. Second, EJR coverage increases price informativeness by producing incremental information and by disciplining managerial information disclosure. Moreover, the coverage of S&P’s – a CRA that is compensated by rated firms – has no impact on rated firms’ transparency. These results lead to the conclusion that investor-paid CRAs play a meaningful governance role due to the absence of conflict of interest that plagues issuer-paid CRAs. Chapter two studies a type of questionable researcher practice: p-hacking. It contains three sets of analyses. First, among a broad set of experimental accounting articles, my co-authors and I document that there is an over-abundance of p-values right below the significance threshold (p = 0.05), and an under-representation of p = 0.06. The finding is consistent with researchers relying on p-hacking to turn insignificant results into significant ones. Second, cross-sectional analyses show that p-hacking is more prevalent among untenured authors, male authors, sole authors, and authors from higher-ranking schools. Lastly, we discussed multiple hypotheses testing methods and disclosure-based solution to guard against p-hacking. Chapter three proposes that gambling preference is a determinant of the significant geographical variation in U.S. firms’ cash holding. Local gambling preference, measured as the ratio of local Catholics to Protestants, is positively associated with local firms’ cash holding. In addition, firms in gambling-prone regions hold more cash only when they are financially constrained, and they invest cash in risky projects such as research & development, which leads to more volatile cash flows. Overall, the results suggest that more cash holding enables gambling-prone firms to take more risks while staying away from financial distress.